2021
DOI: 10.1111/ijlh.13486
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals of white blood cell parameters for healthy adults in japan

Abstract: Introduction While white blood cell (WBC) parameters have been suggested to depend on ethnicity and gender, reference intervals in healthy Asian populations are limited. The present study established reference intervals of WBC parameters for healthy adults in Japan. Methods A total of 750 healthy adults (447 women and 303 men; 18‐67 years old, median 40 years old) at 7 Japanese centers who participated in regular medical checkups entered this study. The WBC parameters were measured using automated hematocytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Male had higher eosinophil counts than female. This sex difference has also been observed in healthy individuals 52 . Estrogen inhibits eosinophil production in the bone marrow and induces eosinophil apoptosis 53 , which might explain higher eosinophil counts in men.…”
Section: Discussionsupporting
confidence: 75%
“…Male had higher eosinophil counts than female. This sex difference has also been observed in healthy individuals 52 . Estrogen inhibits eosinophil production in the bone marrow and induces eosinophil apoptosis 53 , which might explain higher eosinophil counts in men.…”
Section: Discussionsupporting
confidence: 75%
“…The SE and pPNES groups were different in terms of sex, age, history of epilepsy, and number of medical comorbidities. Prior studies have shown that peripheral cell counts and ratios vary with age and sex 35,36 . Studies have also found differences in lactate levels postictally based on gender and seizure type 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that peripheral cell counts and ratios vary with age and sex. 35,36 Studies have also found differences in lactate levels postictally based on gender and seizure type. 24,25 After taking these factors into account neutrophils, monocytes, NLR, NMR, SIRI, SII, and lactate remained different between the SE and pPNES groups.…”
Section: Discussionmentioning
confidence: 99%
“…The criterion for the determination of the neutrophil's nuclear lobulations, especially, the distinction between band-and segmented-neutrophils was published (Takami et al 2021) by the Japanese Society for Laboratory Hematology and Japanese Association of Medical Technologists; this criterion has been widely accepted as the standard among actual observers working at clinical laboratories in Japan. Initially, we adopted this criterion to determine the correct label for each neutrophil's image in the Pre-TR and Pre-TE (Table 1).…”
Section: Methodsmentioning
confidence: 99%